Arte e educação: memorial de formação - Ribeiro, Armando Pereira (2025)
This research is an investigation of my formative journey as a History teacher in the public elementary school system in the northeast of Minas Gerais state. As a Formative Memorial (FM), it was narrative, autobiographical, and qualitative in nature, with the aim of situating myself in the current moment of my career and at the same time constructing a projection of my future performance. Narrative in training contexts (the act of explaining learning processes to oneself and to others) allows for the understanding of the historicity of learning and enables self-regulation of learning methods in an emancipatory direction (Abrahao; Passegi, 2012). The question that guided the construction of the FM was: what is the relationship between art and education in my formative journey and in my professional practice? A theoretical review was carried out on the relationship between art and education with an emphasis on aesthetic experience as a moment of didactic activity. This review sought to support the concepts of education (Freire, 1996; Saviani, 2001), reading the world (Freire, 1996), ethics (Saviani, 2001) as founding moments of pedagogical activity in a school environment. In turn, the concepts of art (Fischer, 1987), aesthetics (Boal, 2009) and experience (Bondía, 2002) served as references for a definition of the concept of “aesthetic experience”. Using these theoretical references, I sought to present the aesthetic experience in the terms defined in this work and practiced throughout my professional activity as a moment that benefits the subjects to elaborate and enunciate readings of the world (Freire, 1996) that, in a dialogical situation (Freire, 1996), allow the construction of knowledge in an educational process that strengthens the autonomy (Freire, 1996; Saviani, 2001) of students and educators. As I sought a historical perspective on training, professional and pedagogical practice, the MF was constructed as an institutional, descriptive and reflective self-writing (Passegi, 2010), which sought to develop a critical reflection on the facts that marked my intellectual formation and my personal and professional trajectories. In this endeavor, two concepts were fundamental: “formative experiences” and “reference memories” (Josso, 2004).